Readability Level of the National and Social Education Textbook among the Fourth Grade Students in Jordan - Jawarneh, Mohammad (Jordan Journal of Educational Sciences, 2008)
The purpose of the study was to determine the readability level of national and social education textbook among the fourth grade students in Jordan, and to explore the effect of gender on the readability level, and the text order according to the readability level of the textbook. Four cloze tests of different topics of the textbook were set up to measure the readability level; these tests were distributed to a random sample of (300) male and female students in different schools of the first Zarqa Directorate of Education. The study results revealed that students’ performance in the readability level of the textbook was low, and that there were significant differences in the readability level of the textbook due to gender. These difference were in favor of the female students. The findings also revealed that the reading texts in the textbook were not scaled according to the readability level